Advances in RNA Epigenetic Modifications in Hepatocellular Carcinoma and Potential Targeted Intervention Strategies - Zhu, Li-Ran; Ni, Wei-Jian; Cai, Ming; Dai, Wen-Tao; Zhou, Hong (Frontiers in Cell and Developmental Biology, 2021)
The current interventions for hepatocellular carcinoma (HCC) are not satisfactory, and more precise targets and promising strategies need to be explored. Recent research has demonstrated the nonnegligible roles of RNA epigenetic modifications such as N6-methyladenosine (m6A) and 5-methylcytosine (m5C) in various cancers, including HCC. However, the specific targeting mechanisms are not well elucidated. In this review, we focus on the occurrence and detailed physiopathological roles of multiple RNA modifications on diverse RNAs closely related to the HCC process. In particular, we highlight fresh insights into the impact mechanisms of these posttranscriptional modifications on the whole progression of HCC. Furthermore, we analyzed the possibilities and significance of these modifications and regulators as potential therapeutic targets in HCC treatment, which provides the foundation for exploring targeted intervention strategies. This review will propel the identification of promising therapeutic targets and novel strategies that can be translated into clinical applications for HCC treatment.